Alien plants of Europe: introduction pathways, gateways and time trends - Margarita Arianoutsou; Ioannis Bazos; Anastasia Christopoulou; Yannis Kokkoris; Andreas Zikos; Sevasti Zervou; Pinelopi Delipetrou; Ana Cristina Cardoso; Ivan Deriu; Eugenio Gervasini; Konstantinos Tsiamis (PeerJ, 2021)
The Convention on Biological Diversity (CBD) pathways classification framework used in the implementation of the European Union’s (EU) Regulation 1143/2014 on invasive alien species (IAS Regulation) has recently been adopted by the European Alien Species Information Network (EASIN), the official information system supporting the implementation of the IAS Regulation. In the current paper, the result of an alignment of the primary introduction pathways of all alien plants in Europe included in the EASIN catalogue is presented, based on the CBD framework. In total, 6,250 alien plant taxa (marine plants excluded), both alien to Europe (native range outside Europe) and alien in Europe (native range partially in Europe) are reported. Altogether 5,175 plant taxa had their primary introduction pathway aligned based on the CBD framework, while for the rest the pathway remains unknown. In addition, the taxonomy, year and country of its first record in the wild are provided for each taxon. Our analyses reveal that the main primary introduction pathways of alien plants into Europe are linked to accidental escapes from ornamental and horticultural activities. Northwestern European countries seem to act as the main gateway areas of alien plants into Europe. Recent first observations of new alien taxa growing spontaneously exhibit a contemporary accelerating trend for plants alien to Europe, particularly linked to ornamental and horticultural activities. On the other hand, the number of new plants alien in Europe seems to have stabilized over the last few decades. The present work can assist in the prioritization of introduction pathways control, with the target of slowing down the rate of alien plants introductions into Europe, following also the requirements of the IAS Regulation.